Mobile application luggage tracking system using GPS module and NodeMCU / Nurul Fitriah Abdulham and Noorhayati Mohamed Noor - Abdulham, Nurul Fitriah; Mohamed Noor, Noorhayati (Universiti Teknologi MARA, 2023)
In this paper, a mobile application for luggage tracking system to track a misplaced or stolen luggage is designed. The application is to help traveller to track their misplaced luggage or stolen in public places. The luggage tracking system is a prototype of device tracker using a GPS and NodeMCU which will be kept inside a luggage. The device will be tracked via GPS satellites and send the data to the GPS module, and the luggage's owner will be informed of its whereabouts through the mobile application. The luggage tracking system uses wireless communication, which is Wi-Fi with the assistance of a microcontroller for location transmission. This project system also includes a mobile application to track and trace the luggage's position using Google Map with a marker on it.